The Role of the Comptroller in measuring the level of public disclosures in the annual management report of public sector units in accordance with the criteria of the Global reporting Initiative (GRI) - Osama Tariq Abbas; Wafaa Abd Al-Ameer Al-Dabbas (Journal of Madenat Alelem University College, 2021)
This research aimed to prepear a program to examine and scrutinize the contents of the annual management report if the (GRI) standards are applied. The content of this program has been based on a study of the criteria of the Global reporting Initiative, which aims to report sustainability in the light of recent global trends toward sustainable development and the direction of institutions and economic units in different countries toward the neutralization of the commitment of their activities to sustainability in their dimensions (Institutional, economic, environmental and social); In addition to numerous research and studies that emphasized the need to expand disclosure toward transparency and accountability, the auditing profession is no longer limited to the financial function mainly to verify its integrity and credibility, and has kepatpace with contemporary developments to include the provision of other services, non-financial services, including services The assurance of the implementation of the GRI standards, in the light of which the level of public disclosures has been checked and measured to verify their safety and adequacy. The researchers reached a set of conclusions, the most important of which are: (1) the presence of an important role of the Comptroller in providing the sustainability reporting emphasis service and in the light of the GRI standards and in determining the level and degree of disclosure of financial and non-financial information.(2) The absence of a certified module for external auditors to examine and measure the level of application and use of the Gri standards for sustainability disclosure. (3) The results showed that the level of disclosure of (GRI) indicators for public disclosures was low (0.27). In addition, there is a relationship between the implementation of the Global reporting Initiative (GRI) and the increased level of transparency in the disclosure of information in the annual management report